Face to Face: facial close-ups and joint attention in Science and the Visual Arts - Kinder, Marsha (Lumina, 2017)
This essay examines the contrasting visions of the expressive powers of the human face—both from neuroscientific approaches rooted in Darwin which argue for a codified system of six basic emotions universally recognized (happiness, sadness, anger, fear, disgust, surprise) and from the visual arts of cinema, television and portraiture painting that rely on facial close-ups to represent an emotional fluidity that is always subjective. As a means of reconciling the two approaches, it turns to the current study of infants by developmental psychologists (like Peter Mundy and Daniel Stern) who stress the importance of an infant’s ability to read the mother’s face, which facilitates joint attention, the acquisition of verbal language and social interactions with the world. Although Stern’s imaginative dialogues sound literary and subjective, his description of the infant’s encounter with the mother’s face is actually consistent with the explanation by neuroscientist Antonio Damasio (1999) of how consciousness is first launched in the “core self.” By treating the mother’s face as the crucial object in the infant’s early development and by perceiving this encounter awash in reflective feelings (which Damasio distinguishes from basic emotions shared with other species), he helps explain the dichotomy between the two systems of emotive facial expressions: reading the specific codified emotions (in humans and other species) versus experiencing the flow of (what Damasio calls) “background feelings” that continuously play across the human face. By emphasizing the theories of Béla Balázs and films of Ingmar Bergman and Chick Strand, which literally teach us how to read these background feelings moving across the human face, this essay claims facial close-ups do not distract us from our social circumstances or political action as Walter Benjamin argued. Instead they can have an ideological edge in a wide range of genres as they enable us to see this emotional engagement in joint attention both as a form of interpellation and as a means of survival—not only for infants but for all those engaged with the visual narrative arts.